Indicadores de sustentabilidade de reservatórios no semi-árido brasileiro: uma proposta para a bacia do rio Jaguaribe - Ceará - Santos, Marcelo Brauner dos (2009)
From all the natural phenomena that afflict the region of Jaguaribe River Basin, the drought is certainly the most damaging. The manner found, with the passing of the years, to overcome this adversity is to build superficial water reservoirs, as a mean to assure their flow during the droughts. The problem is that the building of most of those reservoirs was executed without a detailed study of their hydrologic sustainability, resulting in the construction of a great number of inefficient reservoirs. The solution to this problem is based on the responsible management of the existing reservoir network and the realization of sustainability studies on future projects. To make this possible, tools capable of measuring the reservoir sustainability, as well as indexes and indicators, become necessary. We have searched the literature about Indicators and indexes of sustainability and adapted them to the situation of the Jaguaribe River Basin. From this research, a set of measurements formed by indicators of reliability, resiliency, vulnerability and the sustainability index of the Jaguaribe, that measures the hydrologic sustainability of the reservoir. To realize this case study, 34 reservoirs located in the Jaguaribe River Basin were used, which were simulated for 12 different scenarios, varying their capacities and outflows to obtain dimensonless capacity factors (fK) equal to 1, 2, 4 and the real one. Also to obtain release dimensonless factors (fM) equal to 0.25, 0.5 and 0.75. The results obtained for this set of measurements were consistent and revealed that the studied reservoirs, in general, were classified as reservoirs of low hydrologic sustainability.